Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

(Will l give 25 points!) Solve the system of linear equations by substitution. -8x + y = 5 and 5x - y = 3

Sagot :

Answer:

x = -8/3 and y = -49/3

Step-by-step explanation:

(Step 1) To solve using substitution, you first need to isolate a variable in one of these equations. I chose to isolate "y" in the following equation.

-8x + y = 5                                        <--- Original equation

y = 5 + 8x                                         <--- Add 8x to both sides

(Step 2) Now, substitute (5 + 8x) for "y" in the second equation.

5x - y = 3                                          <--- Original equation

5x - (5 + 8x) = 3                               <--- Substitute 5 + 8x for "y"

5x - 5 - 8x = 3                                  <--- Distribute (-) in the parentheses

-3x - 5 = 3                                        <--- Combine terms with "x"

-3x = 8                                              <--- Add 5 to both sides

x = -8/3                                             <--- Divide both sides by -3

(Step 3) Since you know the value of "x", plug it into one of the equations to solve for "y".

y = 5 + 8x                                         <--- Original (rearranged) equation

y = 5 + 8(-8/3)                                   <--- Plug (-8/3) for "x"

y = 5 - 64/3                                       <--- Multiply

y = 15/3 - 64/3                                   <--- Convert 5 into a fraction

y = -49/3                                           <--- Subtract

(Step 3.5) You can check your work by plugging "y" into the other equation to see if the answer for "x" is the same.

5x - y = 3                                             <--- Original equation

5(-8/3) - y = 3                                      <--- Plug (-8/3) for "x"

-40/3 - y = 3                                        <--- Multiply

-40/3 - y = 9/3                                     <--- Convert 3 into a fraction

-49/3 - y = 0                                        <--- Subtract both sides by 9/3

-49/3 = y                                             <--- Add both sides by "y"

The value of the system of equations is x = -8/3 and y = -49/3.

this question is hard what the heck